Studi Literatur: Jiwa Kewirausahaan Etnis Minangkabau (Minang Entrepreneuship) - Relifra; Nova Suryani; Eko Fikriando (Teewan Journal Solutions, 2024)
The success of entrepreneurship is determined not only by economic factors, but also by the cultural influences that shape individual attitudes, values, and behaviour in running a business. The purpose of this study is to look at the characteristics of ethnic Minangkabau entrepreneurship influenced by culture. The method used in this research is the method of studying literature with Scopus and Google Scholar sources obtained through the Publish or Perish application. (PoP). Entrepreneurial characteristics of Minangkabau ethnicity include their confidence, hard work, contribution to the family, careful calculation, independence, perseverance, consistency, ingenuity, flexibility, and courage to face business challenges.